Aborto : uma discussão ética - Silva, Vera Lucia Mariani da (My University, 2014)
This essay has as main objective analyze the perspective trough ethics. It will attempt to answer some related questions about the abortion’s ethics, the situations where is ethically allowable the act of abortion, if the abortion is understanding as wrong ever or if could exist situations where abortions turns ethically allowable, also the questions related to the fetus as a persona. Likewise, questions the damage existences or not in conducting an unwanted fetus pregnancy. The argumentation’s building process is given utilizing the Thomson’s article originally published in 1971 and the Schwarz’s published in 1992. The substantiation will be based in Bioethics and Utilitarianism, in addition to, this essay review historical abortion’s roots, from the persona definition and the possibility of determine where human life begins.
Esta dissertação tem por objetivo analisar o aborto através da perspectiva da ética. Tentará responder algumas questões relacionadas à ética no aborto, as situações em que é eticamente permissível abortar, se o aborto é entendido como errado sempre ou existem situações em que se torna eticamente aceitável, além de questões relacionadas à personalização do feto. Questiona também a existência ou não, de danos ao conduzir uma gestação de um feto não desejado. Para construir a argumentação será utilizando o artigo de Thomson, publicado originalmente em 1971, e o de Schwarz publicado em 1992. A fundamentação será baseada na Bioética e no Utilitarismo, além da revisão das raízes históricas do aborto, da definição de pessoa e da possibilidade de definir quando começa a vida humana.
Keywords: Aborto; Ética; Bioética; Filosofia; Abortion; Ethics; Bioethics; Philosophy